Big Data Analytics and Other Emerging Technologies: The Impact on the Australian Audit and Assurance Profession. Issue 4 (20th May 2020) - Kend, Michael; Nguyen, Lan Anh
Abstract: The aim of this exploratory research study is to obtain the views of relevant stakeholders in relation to the impact big data analytics (BDA), artificial intelligence (AI) and robotics have had in Australia on the audit and assurance services market. Views are also sought on the impact or potential for impact of blockchain technologies. This paper reports findings from interviews and/or focus groups with 20 individuals representing key stakeholders in the market for audit and assurance services in Australia. Via a synthesis of these stakeholder perceptions and a review of the relevant accounting literature, the study finds that, overall, the impact of BDA, robotics and AI on auditing is seen as positive. BDA takes auditors away from manual, intensive tasks, and gives them more time to apply their minds and skills to more critical evaluation‐type work or key audit judgements. Participants also highlighted the need for regulators and standard setters to keep on track with the fast‐paced IT, automation evolution in the auditing field. Finally, and surprisingly given the attention surrounding blockchain technologies, the participants in this study seemed unconvinced of the application of blockchain technologies in auditing practice. Abstract : This paper reports findings from interviews and/or focus groups with 20 individuals representing key stakeholders in the market for audit and assurance services in Australia. Via a synthesis of these stakeholder perceptions and a review of the relevant accounting literature, the study finds overall, the impact of BDA, robotics and AI on auditing in Australia is seen as positive.